To solve for r, we will isolate the variable on one side of the equation.
Let's start by removing the negative sign near the 6:
r/5 - 6 = -1
Next, we will add 6 to both sides of the equation to isolate the term with r:
(r/5) + 6 = -1 + 6
This simplifies to:
(r/5) + 6 = 5
Now, let's subtract 6 from both sides to isolate the term with r:
(r/5) = 5 - 6
This simplifies to:
(r/5) = -1
Finally, to solve for r, we will multiply both sides of the equation by 5:
5 * (r/5) = -1 * 5
The 5 on the left side cancels out, which leaves us with:
r = -5
Therefore, the solution is r = -5.
Solve for r.
r over 5−6=−1
1 answer